Cytosolic protein translation regulates cell asymmetry and function in early TCR activation of human CD8+ T lymphocytes - Gómez-Morón, Álvaro; Tsukalov, Ilya; Scagnetti, Camila; Pertusa, Clara; Lozano-Prieto, Marta; Martínez-Fleta, Pedro; Requena, Silvia; Martín, Pilar; Alfranca, Aranzazu; Martin-Gayo, Enrique; Martin-Cofreces, Noa B (Frontiers in Immunology, 2024)
Introduction CD8+ cytotoxic T lymphocytes (CTLs) are highly effective in defending against viral infections and tumours. They are activated through the recognition of peptide–MHC-I complex by the T-cell receptor (TCR) and co-stimulation. This cognate interaction promotes the organisation of intimate cell–cell connections that involve cytoskeleton rearrangement to enable effector function and clearance of the target cell. This is key for the asymmetric transport and mobilisation of lytic granules to the cell–cell contact, promoting directed secretion of lytic mediators such as granzymes and perforin. Mitochondria play a role in regulating CTL function by controlling processes such as calcium flux, providing the necessary energy through oxidative phosphorylation, and its own protein translation on 55S ribosomes. However, the effect of acute inhibition of cytosolic translation in the rapid response after TCR has not been studied in mature CTLs. Methods Here, we investigated the importance of cytosolic protein synthesis in human CTLs after early TCR activation and CD28 co-stimulation for the dynamic reorganisation of the cytoskeleton, mitochondria, and lytic granules through short-term chemical inhibition of 80S ribosomes by cycloheximide and 80S and 55S by puromycin. Results We observed that eukaryotic ribosome function is required to allow proper asymmetric reorganisation of the tubulin cytoskeleton and mitochondria and mTOR pathway activation early upon TCR activation in human primary CTLs. Discussion Cytosolic protein translation is required to increase glucose metabolism and degranulation capacity upon TCR activation and thus to regulate the full effector function of human CTLs.